Determinants of career success: a case study of male teachers in secondary schools - Salahudin, Shahrul Nizam; Ramli, Hani Suhaila; Abd Razak, Muhammad Helmy; Abdullah, Muhammad Safizal; Masum, Ahmad (2021)
Malaysian secondary schools are facing a shortage of male teachers. Almost 70% of the teaching profession is dominated by female teachers. There is an obvious gap in the reason why teaching is not preferred by the male gender. This study intends to find the determinants of career success among male teachers with the hope of revealing the career success factors that are associated with male teachers. A survey was done among 140 male teachers in secondary schools in the state of Malacca, Malaysia. Results showed that 4out of 5 of the determinants factors are significantly explaining career success among the teachers (Emotional Intelligence, Person-Job-Fit, Career Adaptability & Work-Life Balance) while one is unable to explain the career success of the teachers (Career Commitment). The findings enable policymakers to prioritize and draft better career development plans for the teachers that focus on issues about the recruitment of more emotional intelligence teachers, optimize person-job-fit and designing jobs that emphasize work-life balance.